One‐Pot and Regioselective Gold‐Catalyzed Synthesis of 2‐Imidazolyl‐1‐pyrazolylbenzenes from 1‐Propargyl‐1H‐benzotriazoles, Alkynes and Nitriles through α‐Imino Gold(I) Carbene Complexes. Issue 9 (17th March 2016) - González, Jairo; Santamaría, Javier; Suárez‐Sobrino, Ángel L.; Ballesteros, Alfredo
Abstract: A three‐component gold(I)‐catalyzed synthesis of 2‐imidazoyl‐1‐pyrazolylbenzenes from 1‐propargyl‐1 H ‐benzotriazoles is described here. Initially the benzotriazole derivative suffers an intramolecular 5‐ endo ‐ dig cyclization to form a triazapentalene. This dipolar compound is able to perform an intermolecular and regioselective attack to a gold‐activated alkyne. After triazole breakage, the pyrazole ring and an α‐imino gold carbene complex are formed. Finally, the iminocarbene is captured by a nitrile to form an imidazole ring. Abstract :